Structural & functional characterization of 3-Deoxy-d-arabino-heptulosonate 7-phosphate synthase from Helicobacter pylori & Mycobacterium tuberculosis : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Biochemistry at Massey University, Turitea, Palmerston North, New Zealand - Webby, Celia Jane (Massey University, 2006)
The shikimate pathway, responsible for the biosynthesis of aromatic compounds, is found in microorganisms and plants but absent in higher organisms. This makes the enzymes of this pathway attractive as targets for the development of antibiotics and herbicides. Recent gene disruption studies have shown that the operation of the shikimate pathway is essential for the viability of M. tuberculosis, validating the choice of enzymes from this pathway as targets for the development of novel anti-TB drugs. 3-Deoxy-D-arabino-heptulosonate 7-phosphate synthase (DAH7PS) catalyzes the first committed step of the shikimate pathway. Two distinct classes of DAH7PS have been defined based on sequence similarity. The type I DAH7PSs are well characterized, however prior to this project there was limited mechanistic and no structural information about type II enzymes. Sequence identity between type I and type II enzymes is less than 10% raising the possibility that they represent distinct protein families, unrelated by evolution. We have functionally characterized the type II enzyme from Helicobacter pylori, and have shown that type I and type II enzymes catalyze a metal-dependent ordered sequential reaction following the same stereochemical course. We have solved the structure of the type II DAH7PS from M. tuberculosis using single-wavelength anomalous diffraction (SAD) methods and the structure reveals a tightly associated dimer of (β/α)8 TIM barrels. The monomer fold, the arrangement of key residues in the active site, and the binding modes of PEP and Mn2+, all match those of the type I enzymes. This similarity of protein fold and catalytic architecture makes it unequivocal that type I and type II enzymes are related by divergent evolution from a common ancestor. Interestingly, there are significant differences in the additional structural elements that extend from the core (β/α)8 barrel and in the quaternary structure. Further structural and functional analysis of M. tuberculosis DAH7PS revealed that the two major additions decorating the barrel are involved in the binding of the aromatic amino acids. Two distinct inhibitory binding sites for Trp and Phe have been identified providing an explanation for the synergistic inhibition displayed with Trp and Phe. The role of several active site residues of Mt-DAH7PS in enzyme catalysis has also been investigated.
Content removed due to copyright restrictions: Webby, C.J., Patchett, M.L. & Parker, E.J. (2005) Characterization of a recombinant type II 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase from Helicobacter pylori. Biochemical Journal 390, 223-230 Webby C.J., Lott J.S., Baker H.M., Baker E.N., & Parker E.J. (2005) Crystallization and preliminary X-ray crystallographic analysis of 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase from Mycobacterium tuberculosis. Acta Crystallographica Section F - Sturctural Biology and Crystallization Communications 61(4) 403-406. Webby C.J., Baker H.M., Lott J.S., Baker E.N. & Parker E.J. (2005) The structure of 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase from Mycobacterium tuberculosis reveals a common catalytic scaffold and ancestry for type I and type II enzymes. Journal of Molecular Biology 354(4), 927-939
Keywords: Shikimate pathway; Microbial enzymes; Fields of Research::270000 Biological Sciences::270100 Biochemistry and Cell Biology::270108 Enzymes